Congreso de Historia de los pueblos de la Provincia de Santa Fe I, 1982-nov.8-10, Santa Fe. Puerto Reconquista (MINISTERIO DE GOBIERNO, 2002)
CONTENIDO : RAVAZZOLA DE GASTALDO, ANA MARIA COORD.; URQUIZA, CESAR DE; PENA DE URQUIZA, MARIA ROSA; ROSSI DE BENVENUTTI, JULIA